Concomitant dimorphs of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates with different halogen bonding contacts: first order crystal-to-crystal thermal phase transition of kinetic form to the thermodynamic form - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S.; Sanki, A. K. (Chemical Communications, 2005)
Crystallization of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates from ethyl acetate-petroleum ether solution produced concomitant dimorphs that have different halogen bonding contacts; the kinetic form with C-(BrO)-O-...-C contacts upon heating to 185 degrees C, converts completely to the thermodynamic form with C-(BrOLC)-O-... contacts via crystal-to-crystal first order phase transition.